An Intervention Framework to Facilitate Psychological Trauma Management in High-Risk Occupations - Jonker, Bouwer E.; Graupner, Lene Ilyna; Rossouw, Lizelle (Frontiers in Psychology, 2020)
A variety of psychological trauma management programmes are available to assist employees who were exposed to a traumatic event in the workplace. There is, however, limited literature available on how these programmes are experienced by employees in high risk occupations. This study qualitatively explored the experiences of psychological trauma management programmes from the perspective of employees working in three high risk occupations. The purpose of this study was to explore the experiences of the participants from the three high risk occupations in order to compile a framework to support and improve productivity and wellbeing of employees affected by work-related trauma. A qualitative research design following an interpretivism and social constructivism approach was employed. A multiple-case study was used as research strategy incorporating three sectors in South Africa, i.e. mining, policing and emergency medical services. Data was gathered by means of semi-structured interviews and focus groups, and analysed using thematic analysis. The findings across the three sectors showed that the participants viewed multiple counselling sessions, face-to-face counselling, regaining control, support from social workers and colleague support as effective strategies to manage psychological trauma. Strategies that were viewed as ineffective included: inability of counsellors to relate to the participants’ experiences, telephonic counselling, compromised objectivity, lack of supervisor support, lack of counselling availability and specialised skills, premature resuming of duties and a single dimension approach. Finally, an intervention framework is proposed to address psychological trauma in high risk occupations.